EZH2 Is Essential for Fate Determination in the Mammalian Isthmic Area - Wever, Iris; Wagemans, Cindy M. R. J.; Smidt, Marten P. (Frontiers in Molecular Neuroscience, 2019)
The polycomb group proteins (PcGs) are a group of epigenetic factors associated with gene silencing. They are found in several families of multiprotein complexes, including Polycomb Repressive Complex (PRC) 2. EZH2, EED and SUZ12 form the core components of the PRC2 complex, which is responsible for the mono, di- and trimethylation of lysine 27 of histone 3 (H3K27Me3), the chromatin mark associated with gene silencing. Loss-of-function studies of Ezh2, the catalytic subunit of PRC2, have shown that PRC2 plays a role in regulating developmental transitions of neuronal progenitor cells; from self-renewal to differentiation and the neurogenic-to-gliogenic fate switch. To further address the function of EZH2 and H3K27me3 during neuronal development we generated a conditional mutant in which Ezh2 was removed in the mammalian isthmic (mid-hindbrain) region from E10.5 onward. Loss of Ezh2 changed the molecular coding of the anterior ventral hindbrain leading to a fate switch and the appearance of ectopic dopaminergic neurons. The correct specification of the isthmic region is dependent on the signaling factors produced by the Isthmic organizer (IsO), located at the border of the mid- and hindbrain. We propose that the change of cellular fate is a result of the presence of Otx2 in the hindbrain of Ezh2 conditional knock-outs and a dysfunctional IsO, as represented by the loss of Fgf8 and Wnt1. Our work implies that next to controlling developmental transitions, EZH2 mediated gene silencing is important for specification of the isthmic region by influencing IsO functioning and repressing Otx2 in the hindbrain.